Sociolinguistics: historical path of the constitution of sociolinguistics as a science - de Oliveira, João Paulo; Carlos Santana de Souza, Antônio (Seven Editora, 2023)
One of the linguistic ideas of the beginning of the 20th century was that the linguistic object should be identified with a part of the reflection material of the oral, verbal and written forms. In the second half of the century, Sociolinguistics represented and still represents linguistic diversity by introducing the concept of linguistic variations. This article aims to present a review of the assumption swhere the speaker is categorized as the agent producer of his discourses, as a result of the idea of the flexibility of language as a legitimate place for the construction of speech in the spaces where it occurs. This article aims to rescue some of the history of pre-language studies that contributed to the constitution of the Variationist Sociolinguistic Theory. In this sense, we briefly recover the history of languages from the 18th to the 20th centuries, taking into account important facts concerning linguistic diversity and variation, in the context of the following methods: comparative studies, historical comparison. subjects, neogrammatics, dialectology, Structuralism. DOI: https://doi.org/10.56238/tfisdwv1-062